Assessment of reproductive health educatrion in Srilankan Schools. - Senaratna, B .C.V (My University, 2003)
Teachers percived their knowledge to be inadequate.Their sources of RH information were limited.Their teaching skills were percived to be inadequate partly due to the low knowledge in some RH contents areas,but more due to inadequate skills training they had received and persisting cultural variables.Unfavorable opinions in some teachers regarding RHEP,from the science subject curriculam were found to be adversely affecting current RHEP.In order to improve current RHEP,it is recommended that:RH as applied to school curriculam be cl;early defined widening and deepening contents;all curriculam developers be aware of past experiences of the RHEP and factors affecting attitudes and behavior of the adolescents;role of other organizations be considerd in RHEP;teachers' skills and knowledge be improved;both teachers' and students access to RH contents;and distribution of RH contents under different subjects be done in a complementing manner,or, alternatively,be taught under a single subject.